Central nervous system involvement with multiple myeloma: long term survival can be achieved with radiation, intrathecal chemotherapy, and immunomodulatory agents. (15th June 2013) - Chen, Christine I.; Masih‐Khan, Esther; Jiang, Haiyan; Rabea, Ahmed; Cserti‐Gazdewich, Christine; Jimenez‐Zepeda, Victor H.; Chu, Chia‐Min; Kukreti, Vishal; Trudel, Suzanne; Tiedemann, Rodger; Tsang, Richard; Reece, Donna E.
Summary: Involvement of the central nervous system (CNS) in multiple myeloma (MM) is a rare complication, with reported survival of <6 months. This report describes 37 MM patients with leptomeningeal and/or parenchymal brain involvement treated at our institution and identifies factors associated with long‐term survival. From January 1999 to December 2010, 37 patients with CNS MM were evaluated at our institution. Clinical characteristics, treatment and survival were retrospectively collected. CNS disease was present at MM diagnosis in 24% and at relapse in 76%. Plasma cell leukemia (40%) and skull plasmacytomas (65%) were common, suggesting haematological and contiguous spread. Intrathecal (IT) chemotherapy was used in 81%, cranial and/or spinal irradiation in 78%, and various systemic therapies [immunomodulatory agents (IMiDs) (51%), cisplatin‐based (DPACE; cisplatin, doxorubicin, cyclophosphamide, etoposide) (27%), bortezomib (19%), alkylators (11%), dexamethasone alone (8%), auto‐transplant (5%)]. Median survival from CNS disease was only 4·6 months [95% confidence interval (CI): 2·8–6·7]; however, nine patients had prolonged survival (median: 17·1 months, 95% CI: 13·2–67·4). In general, these long‐term survivors were treated with radiotherapy, multi‐dosing IT chemotherapy, and IMiD‐containing therapy. CNS MM is a highly aggressive disease but in our experience, long‐term survival can be achieved with the combination of multi‐dosing IT chemotherapy, radiation and IMiD‐based therapy.